Adaptation of Habrobracon hebetor (Hymenoptera: Braconidae) to Rearing on Ephestia kuehniella (Lepidoptera: Pyralidae) and Helicoverpa armigera (Lepidoptera: Noctuidae). Issue 1 (2nd February 2016) - Borzoui, Ehsan; Naseri, Bahram; Mohammadzadeh-Bidarani, Mozhgan
Abstract: Food characteristics strongly regulate digestive enzymatic activity of insects through direct influences on their midgut mechanisms. Insect performance is better on diets that contain nutrients in proportions that fit its digestive enzymes. Little is known about the influences of rearing history on parasitism success of Habrobracon hebetor Say. This research focused on the effect of nutrient regulation on survival, development, and parasitism of H. hebetor . Life history and digestive enzyme activity of fourth-stage larvae of H. hebetor were studied when reared on Ephestia kuehniella Zeller. This parasitoid was then introduced to Helicoverpa armigera (Hübner), and above-mentioned parameters were also studied in the first and fourth generations after transfer. In term of parasitism success, H. hebetor preferred E. kuehniella over He. armigera . When the first and fourth generations of He. armigera -reared H. hebetor were compared, the rearing history affected the life history and enzymatic activity of the parasitoid. A better performance of H. hebetor was achieved after it was reared on He. armigera for the four generations. Because, digestive α-amylase and general protease of the parasitoid were matched with the new host, it used reserve energy for a better performance. Thus, a better performance of H. hebetor could be obtained when the parasitoid was reared on its original host for at least four generations.